ANALISIS GREEN INOVATION DAMPAKNYA TERHADAP KEUNGGULAN BERSAING PRODUK DAN KINERJA PEMASARAN (STUDI EMPIRIK PADA UKM BATIK CIWARINGIN KABUPATEN CIREBON) - Lili Karmela Fitriani (Research Center and Case Clearing House PPM School of Management, 2015)
This paper examines the relationship between green product innovation, green process innovation, competitive advantage of product and market performance in the SMEs Ciwaringin batik Cirebon West Java. A survey of 93 SMEs batik provides the basis for the empirical investigation. The relationships between the green innovation product, competitive advantage of product and market performance are examined using stepwise regression.The findings show that green product innovation not contributes positively to competitive advantage of product and market performance. Another findings of this study is that the impact of green process innovation contributes positively to competitive advantage of product but not to market performance in the SMEs Ciwaringin batik. Competitive advantage of product has impact to market performance. This paper also discusses the recomendations of the results.